Nonlinear EVM Based on Support Vector Regression Growth Model for Predicting Project Completion Time - Tri Joko Wahyu Adi; Arif Abadil Ghullam (Direktorat Riset dan Pengabdian Kepada Masyarakat, 2022)
Earned Value Management (EVM) is a method used to monitor and to predictproject completion time. This method uses a linear approach in predictingproject time completion. Unfortunately, most of the projects run in dynamicenvironments with complex characteristics, causing project progress torequire a non-linear approach. That is why the use of EVM in monitoring andpredicting non-linear project completion time is less effective. This studyproposes a more realistic alternative approach using non-Linear EVM basedon the Support Vector Regression (SVR) - Growth Model. The SVR-growthmodel is used to accommodate the non-linear progress of the project, while theEVM is used to represent the predicted results of the project completion time.For model validation, 5 data on oil and gas field development constructionprojects in Jawa, Bali and Nusa Tenggara Regions were used as case studies.The results of this study indicate that the results of project completion timeprediction using the SVR-Growth Model provide high accuracy and precisioncompared to the traditional EVM method.